2017
DOI: 10.1186/s12885-017-3352-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent CXCR4 targeting peptide as alternative for antibody staining in Ewing sarcoma

Abstract: BackgroundEwing sarcoma is an aggressive, highly metastatic primary bone and soft tissue tumor most frequently occurring in the bone of young adolescents. Patients, especially those diagnosed with a metastatic disease, have a poor overall survival. Chemokine receptor CXCR4 has a key pro-tumorigenic role in the tumor microenvironment of Ewing sarcoma and has been suggested to be involved in the increased metastatic propensity. Earlier studies on CXCR4 protein expression in Ewing sarcoma yielded contradictory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…A surfaceome study of ES by Town et al showed no expression of CXCR4 in MSC, which makes CXCR4 an attractive target for targeted imaging. Sand et al studied membranous CXCR4 expression in ES cell lines using a fluorescently labeled CXCR4 targeting peptide (MSAP‐Ac‐TZ14011), indicating the feasibility of this agent for FGS. The first in human experience with a radiolabeled version of a similar peptide (Pentixafor) in a small and heterogeneous patient cohort did not completely fulfill the expectations in comparison with standard (18)F‐FDG PET …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A surfaceome study of ES by Town et al showed no expression of CXCR4 in MSC, which makes CXCR4 an attractive target for targeted imaging. Sand et al studied membranous CXCR4 expression in ES cell lines using a fluorescently labeled CXCR4 targeting peptide (MSAP‐Ac‐TZ14011), indicating the feasibility of this agent for FGS. The first in human experience with a radiolabeled version of a similar peptide (Pentixafor) in a small and heterogeneous patient cohort did not completely fulfill the expectations in comparison with standard (18)F‐FDG PET …”
Section: Resultsmentioning
confidence: 99%
“…CXCR4/SDF‐1 signaling plays a role in chemotaxis of hematopoietic cells and in neuron generation during embryogenesis and adult life. It is absent in most healthy tissues but upregulated in the tumor microenvironment of many tumor types, where it is associated with metastasis, angiogenesis, and tumor growth . Also in ES CXCR4 is associated with tumor progression and metastasis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[114] Besides, a subset of SPECT/NIRF dual-modal probes for targeted imaging were assembled based on a lysine scaffold: -NH 2 for cyanine fluorophores, -NH 2 for 111 In-DTPA and -COOH for various targeting peptides including cRGD (78), [115] antimicrobial peptide UBI 29−41 (79), [116] and CXCR4 targeting peptide Ac-TZ14011 (80). [117] Unlike most short-lived PET radionuclides, 111 In is suitable for the development of antibody-guided probes owing to its better compatibility with mAbs pharmacokinetics. A case in point is the CAIX-targeting 111 In-girentuximab-IRDye800CW (81), which has shown its feasibility and safety in a phase I study in clear cell renal cell carcinoma patients (NCT02497599) (Figure 14b).…”
Section: Spect/nirfmentioning
confidence: 99%